Approach to Common Visual Complaints Presenting to the Outpatient Neurologist - Greer, Christine; Dinkin, Marc (Seminars in Neurology, 2021)
Visual complaints are commonly encountered by the practicing neurologist. We review assessment of vision loss, diplopia, and positive visual phenomena, all of which require a thoughtful evaluation to localize disease and refine management. While many causative entities are unlikely to cause poor visual outcomes, including dry eyes, migraine, and congenital strabismus, others may threaten vision, life, or both, such as posterior communicating artery aneurysms, pituitary apoplexy, or temporal arteritis. A systematic approach to vision loss and diplopia is reviewed along with focused differential diagnoses.
Keywords: diplopia; vision loss; positive visual phenomena; neuro-ophthalmology